Sustainability of the Implementation Think Talk Write (TTW) in Teaching Writing in Rural Area - Fifi Dwi Pra Aditya; Afrillia Anggreni; Mochtar Marhum; Budi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
Discovering the sustainability of Think-Talk-Write (TTW) instructional strategy in enhancing students’ writing proficiency through pre – experimental design (one group pre-test and posttest) was objective of this research. The population was the eleventh-grade students of SMA Negeri Tolisu where located in rural area in Celebes-Sulawesi. The sample was the students of XI A, which consisted of 18 students who selected by using a purposive sampling technique. The focuses of this research were on organization, vocabulary, grammar, mechanic and limited in descriptive text. By applying paired samples test, it was found that the Sig. 0.000 is lower than (<) 0.05. It means that the hypothesis is accepted or the TTW strategy is statistically effective in improving writing skill of students of SMA Negeri Tolisu. This research implies that the implementation of TTW strategy can be practically defended as one of strategies in teaching writing in rural areas. It builds up students’ critical thinking in developing and organizing ideas, enriching vocabulary and provoking grammar knowledge.